Nd:YAG1064nm laser functions against Sporothrix globosa by inducing PANoptosis via the regulation of ZBP1-induced PANoptosome activation - Yan, Tianyi; Nan, Jinyan; Jiang, Rihua; Chen, Feng; Li, Jinran (Frontiers in Microbiology, 2025)
BackgroundDue to the emergence of drug resistance in recent years, there is a need for new non-pharmacological treatment methods for sporotrichosis. Our previous study demonstrated that the Nd:YAG1064nm laser exhibited remarkable antifungal activity against Sporothrix globosa, but its exact mechanism remains unclear. This study aimed to detect PANoptosis regulatory protein ZBP1 expression in the skin lesions of patients with sporotrichosis, reveal the exact mechanism of Nd:YAG1064nm laser against sporotrichosis, and provide novel targets and methods for the diagnosis, assessment, and treatment of sporotrichosis.Methodology/principal findingsThe ZBP1 level of 60 patients with sporotrichosis (≤3 months; n = 30 and >3 months; n = 30) and 30 HC were retrospectively reviewed using immunohistochemistry. The morphological changes, Hoechst/PI apoptosis and necroptosis preliminary exploration analysis, DNA fragmentation, calcium determination, and metacaspase activation were investigated in vitro. For the in vivo studies, mice were infected with S. globosa and then treated with a laser, and their footpad skin lesions and changes in the histology of tissue samples were compared. Changes in the levels of ZBP1, PANoptosome [RIPK1, RIPK3, Fas-associated death domain protein (FADD), CASP8], pyroptosis (CASP1, GSDMD), apoptosis (CASP3), and necroptosis (MLKL) related proteins were assessed using immunohistochemistry, whereas the levels of interleukin 17 (IL-17) and interferon gamma (IFN-γ) in peripheral blood were tested by enzyme-linked immunosorbent assay. ZBP1 expression was significantly increased in S. globosa-infected patients. Laser treatment effectively inhibited the growth of S. globosa in vitro, destroying its morphological structure, and maybe inducing apoptosis and necroptosis. Moreover, DNA fragmentation, calcium release into the cytoplasm, and metacaspase activation were observed. In addition, laser treatment demonstrated a clear therapeutic effect in animal models of sporotrichosis, which can lead to PANoptosis-related apoptosis, pyroptosis, and necroptosis. Immune response-related macrophages perceive nucleic acid level changes through ZBP1 to recognize S. globosa and induce PANoptosis by activating the PANoptosome (RIPK1/RIPK3/FADD/CASP8) complex with a Th1/Th17 cell response to combat sporotrichosis.ConclusionNd:YAG1064nm laser mediated PANoptosis resistance to sporotrichosis via ZBP1-PANoptosome-PANoptosis pathway.